Is Public-Private Partnership a Significant Factor when Achieving Horizontal Equity in Public Healthcare Resources in Spain? - De-Haro-García, Julia; Caro Navarro, Ángela (Wiley, 2025)
Achieving horizontal equity in the access and use of public health resources is one of the main goals of the 17 Spanish regions. We analyse geographical inequities in the allocation of human and material resources for specialised care in Spanish hospitals, paying attention to the public-private partnership. We measure inequity using Gini, Concentration and Dissimilarity indices, and Lorenz and Concentration curves, and find that regions having fewer resources in the public sector and less public health spending tend to have higher levels of resources in the private sector, which could contribute to achieve horizontal equity in the public health system.
Keywords: Hospitales; Disparidades económicas regionales; Cooperación pública-privada; Servicios de salud; Health resource; Hospitals; Inequity indeces; Public‐private sectors; Regional disparities